DAPTIVE APPLICATION OF METHODS OF EXPERT ASSESSMENT WHEN DETERMINING EFFICIENCY OF IMPLEMENTATION OF TARGET PROGRAMS OF TERRITORIAL SUBJECTS OF THE RUSSIAN FEDERATION - Anna Babich; Lyubov Babich (Вестник Северо-Кавказского федерального университета, 2022)
In article methodical tools by expert assessment of efficiency of implementation of regional target programs which adaptive use allows to identify profitability, legitimacy and special-purpose character of expenditure of budgetary funds are reasonable. The algorithm of carrying out expert estimation of efficiency of implementation of target programs representing the sequence of special procedures of which the expert opinion in which recommendations about management of the budgetary resources are formulated is result is shown. The main problems of estimation of efficiency of target programs at the regional and municipal levels of the Russian Federation are also considered.